염산용액에서 용매추출에 의한 인듐으로부터 주석의 분리 - 이만승; Man Seung Lee; 안종관; Jong Gwan Ahn (대한금속·재료학회지, 53(7), 2015)
Since there are few ores containing indium, it is very important to recover indium from secondary sources, which is essential substance requested in the manufacture of liquid crystal displays. In order to investigate the possibility of developing a process to recover indium from indium-tin-oxide scrap, solvent extraction experiments were done using a synthetic chloride solution containing indium and tin. In these experiments, the concentration of indium and tin was fixed at 1.0 and 0.1 g/L, respectively. In the HCl concentration range from 0.5 to 4M, amines (Aliquat 336, TOA, TEHA) and TBP were employed. The use of TBP and TEHA resulted in the selective extraction of tin over indium, while it was difficult to separate the two elements by extraction with Aliquat 336 and TOA. TEHA was recommend as a potential extractant for the separation of the two metals because only tin could be selectively extracted from the solution at low HCl concentration.